Copper-zinc-tin-sulfur-selenium film, preparation method thereof and copper-zinc-tin-sulfur-selenium film solar cell comprising copper-zinc-tin-sulfur-selenium film
By finely controlling the selenization temperature and time, the problem that the structure and composition of the absorber layer in CZTSSe thin film solar cells is affected by phase evolution is solved, efficient light absorption and hole transport are achieved, and the photoelectric conversion efficiency and device performance are improved.
Patent Information
- Application Number
- CN202411159732.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-01-21
AI Technical Summary
The photoelectric conversion efficiency of CZTSSe thin-film solar cells is mainly due to the influence of the phase evolution during selenization, which leads to high concentrations of defects and defect clusters, limiting the separation and transportation of photogenerated carriers.
By carefully controlling the selenization temperature and time, especially the temperature and time control in the cooling annealing stage, a CZTSSe film with appropriate band gap and good electrical properties can be prepared to achieve efficient light absorption and hole transport.
Achieved stable preparation of high-efficiency CZTSSe thin film solar cells, improved photoelectric conversion efficiency and device performance, and reduced costs.
Smart Images

Figure CN119330314A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technologies of optoelectronic materials, and more specifically, to a copper-zinc-tin-sulfur-selenium thin film and a preparation method thereof, and a copper-zinc-tin-sulfur-selenium thin film solar cell comprising the same. Background Art
[0002] Among many renewable energy sources, solar energy is one of the important development directions.
[0003] At present, thin-film solar cells have become the mainstream of development trends. Copper zinc tin sulfur selenium (Cu2ZnSn(S,Se)4, CZTSSe) thin-film solar cells have the advantages of low cost, non-toxicity, high stability, and high theoretical conversion efficiency. They are expected to become thin-film solar cells with wider applications and lower costs, and have great potential for future development.
[0004] CZTSSe thin-film solar cell devices are mainly composed of substrate, back electrode, absorption layer, buffer window layer and top electrode, that is, substrate / molybdenum (Mo) back electrode / absorption layer (copper zinc tin sulfur selenide thin film, CZTSSe) / cadmium sulfide (CdS) / intrinsic zinc oxide (i-ZnO) / indium tin oxide (ITO) / top electrode (Ni-Al, Ag, Al, Au, etc.).
[0005] The device performance of CZTSSe thin-film solar cells is limited by its multinary CZTSSe semiconductor absorber layer, i.e., the copper-zinc-tin-sulfur-selenide thin film, i.e., the photoelectric conversion efficiency (PCE) of CZTSSe thin-film solar cells depends on the structure and composition of the absorber layer. The CZTSSe absorber layer is affected by the phase evolution that occurs during the selenization process. Therefore, a comprehensive understanding of the phase evolution within the CZTSSe absorber during the selenization process is crucial to improving the performance of CZTSSe thin-film solar cells.
[0006] Due to the narrow phase stability range of the CZTSSe semiconductor absorption layer and the presence of high concentrations of defects and defect clusters, the separation of photogenerated carriers is greatly restricted and the large-scale recombination of carriers inside the absorption layer surface is aggravated.
[0007] Therefore, how to finely control the preparation process of the CZTSSe absorber layer, study the effects of secondary phases, defects and defect clusters on device performance, and strive to prepare high-quality absorber layer films to improve the photoelectric conversion efficiency of CZTSSe thin-film solar cells are issues that urgently need to be addressed. Summary of the invention
[0008] In view of this, the main purpose of the present invention is to provide a method for preparing a copper zinc tin sulfur selenium thin film to improve the photoelectric conversion efficiency of CZTSSe thin film solar cells.
[0009] To achieve the above object, the technical solution of the present invention is as follows: A method for preparing a copper-zinc-tin-sulfur-selenium thin film comprises the following steps: (1) Preparation of CZTS precursor: Add a divalent copper source and a divalent tin source to a solvent, stir to dissolve, then add thiourea and a zinc source, stir until completely dissolved, and obtain a CZTS precursor solution; (2) Spin coating and baking: The obtained CZTS precursor solution is spin coated on the substrate coated with the back electrode and then baked; Repeat the spin coating and baking steps 3 to 10 times to obtain a CZTS precursor film; (3) Selenization: Place the CZTS precursor film in a graphite box filled with selenium particles, place the graphite box in a rapid annealing furnace, heat it to 450~600℃, and perform selenization treatment; then cool it from 500~400℃ to 350℃~300℃ within 10~25min, continue to cool it to 200℃~150℃ within 5~25min, and then naturally cool it to room temperature to obtain a CZTSSe absorption layer.
[0010] In the present invention, compared with Cu + +Sn 4+ (1+4) system, Cu 2+ +Sn 2+ CZTSSe thin films were prepared using the (2+2) system, with significantly reduced costs.
[0011] Preferably, in step (3), the time for cooling from 480°C to 300°C is 20 minutes, and the time for cooling from 300°C to 200°C is 5 minutes.
[0012] It should be noted that the phase evolution of the CZTSSe absorber layer during the selenization process is an important aspect in solar cell manufacturing. During the selenization process, which is usually carried out at high temperatures (about 300-600°C) in the presence of selenium (Se) vapor, the CZTSSe absorber layer film is formed from the CZTS precursor film.
[0013] At the beginning of the selenization process, the precursor film is in the metallic phase, consisting of copper (Cu), zinc (Zn), tin (Sn), and possibly sulfur (S) compounds. When selenium vapor comes into contact with the precursor material, selenium atoms begin to replace sulfur atoms to form CZTSSe. The structure evolves from the initial disordered phase to a more ordered chalcopyrite-like structure. As selenization continues, the formed CZTSSe grains begin to grow, consuming the remaining selenium vapor and incorporating more Cu, Zn, Sn, and Se atoms into the lattice. During this stage, the selenization temperature and selenization time factors have a huge impact on the evolution of the structure.
[0014] In the present invention, by finely controlling the selenization temperature and time, especially the temperature and time control in the cooling annealing stage, CZTSSe has a suitable band gap and good electrical properties, and efficient light absorption and hole transport are achieved, the required material properties and optimized device performance are achieved, and the purpose of stably preparing high-efficiency CZTSSe thin-film solar cells is achieved.
[0015] Furthermore, in step (1), the divalent copper source is C4H6CuO4·H2O, the divalent tin source is SnCl2·2H2O, the zinc source is ZnCl2, the solvent is DMF, and the solid-liquid ratio of the divalent copper source to the solvent is 0.8~1.2g:10ml.
[0016] Of course, the divalent copper source can also be CuCl2·2H2O.
[0017] In the present invention, a solution method is used to prepare CZTSSe thin films, and a green, environmentally friendly, and low-cost solvent, N,N-dimethylformamide (DMF), is selected. DMF is a polar solvent with good solubility and chemical stability. At the same time, O and N in DMF have two Lewis bases, which enables DMF to dissolve many Lewis metal compounds. For Cu 2+ +Sn 2+ (2+2) system, DMF has high solubility and stability, which can promote Cu 2+ +Sn 2+ The redox reaction rate between them reaches the maximum, forming Cu + +Sn 4+ .
[0018] Furthermore, in step (1), the molar ratio of the divalent copper source to the divalent tin source is 1.35-1.45:1, preferably 1.35:1.
[0019] Furthermore, the obtained CZTS precursor solution is placed in air for 5 to 8 hours, preferably 6 hours, before the subsequent spin coating step.
[0020] The inventors found that in the 2+2 system, the CZTS precursor solution has a usage time window, namely the aging time. When the aging time exceeds the optimal time window, Cu will form on the surface of the CZTSSe absorption layer during the selenization process. x The Se secondary phase has high resistance and hydrophobicity, which leads to imperfect deposition of the CdS buffer layer and short circuit of the solar cell, and then the photoelectric conversion efficiency of the cell device is reduced and the device uniformity is reduced. Therefore, the aging time of the CZTS precursor solution is controlled to 5~8h, preferably 6h; which can effectively improve the performance of the subsequent preparation of CZTSSe thin film solar cells.
[0021] Furthermore, in step (1), after adding thiourea to dissolve, hydrochloric acid is added, and then a zinc source is added, wherein the concentration of the hydrochloric acid is 36-45 wt %, and the hydrochloric acid is added at a ratio of 0.8-1.2:10 in terms of volume of hydrochloric acid to volume of solvent.
[0022] Since the CZTS precursor solution has an aging time limit, in order to further eliminate the aging time phenomenon, reduce the experimental time, reduce the cost of experiments and future commercialization, and reduce the gap between the 2+2 system and the 1+4 system, the present invention proposes a strategy of regulating the environment of the CZTS precursor solution with hydrochloric acid. By regulating the environment of the CZTS precursor solution with hydrochloric acid, the association effect is inhibited and the aging phenomenon is eliminated. 2+ and Sn 2+ The redox reaction to Cu + and Sn 4+ Carry out, increase Sn 4 + concentration, not only reduces the V Sn (- / 0), Cu Sn (- / 0) and Zn Sn (2- / -) and other defect concentrations, while reducing experimental costs. The carrier concentration inside the absorption layer is increased, and the influence of the band tail state on the surface of the absorption layer is reduced; the photoelectric conversion efficiency and device uniformity of CZTSSe thin-film solar cells are significantly improved.
[0023] Furthermore, it also includes repeating step (2) and step (3) once to obtain a double-layer CZTSSe absorption layer; specifically: First, a portion of the CZTS precursor film is spin-coated and baked for 2 to 5 times, preferably 3 times, to obtain a portion of the CZTS precursor film, which is then subjected to selenization treatment in step (3) to form a first portion of the CZTSSe absorption layer; the top of the first portion of the CZTSSe absorption layer is spin-coated and baked for 5 to 8 times, preferably 7 times, and then subjected to selenization treatment in step (3) to obtain a double-layer CZTSSe absorption layer.
[0024] Through the above steps, a double-layer absorption layer can be constructed, which significantly improves the quality of small grains at the bottom of the absorption layer. The excellent Cu / Zn and Zn / Sn ratios reduce the Cu Zn Shallow level and Sn Zn The deep level defect concentration increases the V OC and J SC , which can further improve the photoelectric conversion efficiency.
[0025] Furthermore, in step (3), the heating to 450-600° C. for selenization treatment is specifically as follows: First heat to 400~500℃ within 30~90s; Then the temperature is raised to 510~580℃ within 150~250s; Finally, the temperature is lowered to 500-400°C within 600-900s.
[0026] Preferably, firstly heating to 480°C within 60s; Then the temperature was raised to 550°C within 180s; Finally, the temperature was lowered to 480°C within 720s.
[0027] That is, the entire selenization annealing procedure is preferably: 20°C - 60s–480°C–180s–550°C–720s–480°C–1200s–300°C–5 min–200°C– natural cooling–20°C.
[0028] Further fine control of the heating time and temperature during the selenization process can optimize the Mo / CZTSSe and CZTSSe / CdS interface. The thickness of Mo(S,Se)2 is significantly reduced without affecting the thickness of the back electrode, creating favorable conditions for constructing an improved hole transport layer. At the same time, the surface defect concentration of the CZTSSe absorption layer is reduced, reducing the Fermi level pinning at the CZTSSe / CdS interface.
[0029] Furthermore, in step (2), the baking temperature is 260°C.
[0030] When the baking temperature is low, water molecules and impurities cannot be effectively removed after coating multiple layers of the precursor film, so a CZTSSe solar cell with photoelectric conversion efficiency cannot be fully formed; when the baking temperature is 260°C, water molecules and impurities can be completely removed, and less metal elements in the precursor film evaporate, thereby forming a CZTSSe solar cell with the best photoelectric conversion efficiency. When the baking temperature is too high, although water molecules and impurities can be completely removed, the metal elements in the precursor film evaporate to a certain extent, affecting the performance of the CZTSSe solar cell prepared subsequently.
[0031] The present invention also aims to provide a copper-zinc-tin-sulfur-selenium thin film prepared by any of the above-mentioned preparation methods.
[0032] The present invention also aims to provide a copper zinc tin sulfur selenium (CZTSSe) thin film solar cell, comprising the copper zinc tin sulfur selenium thin film described above.
[0033] Compared with the prior art, the present invention has the following advantages: The present invention provides a process for stably preparing high-efficiency copper zinc tin sulfur selenium (CZTSSe) thin films, and controls the phase evolution during the selenization process. By finely controlling the selenization temperature and time, CZTSSe has a suitable band gap and good electrical properties, and achieves efficient light absorption and hole transport, so as to achieve the required material properties and optimize device performance, thereby achieving the purpose of stably preparing high-efficiency CZTSSe thin-film solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a flow chart for preparing the CZTSSe thin film solar cell device in Example 1.
[0035] Figure 2 These are the surface (2a) and cross-sectional (2b) morphologies of the CZTSSe absorption layer films prepared at different aging times in Example 2.
[0036] Figure 3 These are SEM images of the Without HCl and With HCl samples in Example 3, wherein: (a) cross-sectional morphology of With HCl, (b) surface morphology of With HCl, (c) cross-sectional morphology of Without HCl, and (d) surface morphology of Without HCl.
[0037] Figure 4 (a) IV curves, (b) PCE statistical distribution, (c) C-2-V diagram and (d) standard deviation of PCE of the Without HCl and With HCl samples in Example 3.
[0038] Figure 5 These are three experimental methods for preparing the CZTSSe absorption layer in Example 4.
[0039] Figure 6 This is a surface SEM test image of the complete absorption layer and the first part of the absorption layer in Example 4.
[0040] Figure 7 Surface and cross-sectional SEM tests of the actively constructed double-layer absorbent layer in Example 4.
[0041] Figure 8 Surface and cross-sectional SEM images of the CZTSSe absorber layer in Example 4: (a) (d) BASIC, (b) (e) TFS and (c) (f) DA.
[0042] Fig. 9 Box plots of device performance of BASIC, TFS and DA in Example 4: (a) PCE, (b) V OC , (c) J SC , (d) FF, (e) R sh , (f) RS , (g) A, and (h) J0.
[0043] Fig.10 The photoelectric conversion efficiency (PCE) of CZTSSe thin film solar cells at different baking temperatures in Example 5.
[0044] Fig.11 SEM characterization of (a) surface and (b) cross section of the CZTSSe absorption layer film under the first stage of temperature reduction control in Example 6.
[0045] Fig.12 SEM characterization of (a) surface and (b) cross section of the CZTSSe absorption layer film under the second stage temperature reduction control in Example 6.
[0046] Fig.13 The following is a summary of the parameters of the CZTSSe thin film solar cell during the selenization cooling stage in Example 6.
[0047] Fig.14 : This is the X-ray diffraction (XRD) pattern of each CZTSSe absorption layer in Example 7.
[0048] Fig.15 : This is the Raman spectrum (Raman) of each CZTSSe absorption layer in Example 7.
[0049] Fig.16 This is a scanning electron microscope (SEM) image of each CZTSSe absorption layer in Example 7.
[0050] Fig.17 Statistical distribution diagram of the photoelectric conversion efficiency (PCE), open circuit voltage (VOC), short circuit current (JSC), and fill factor (FF) of each copper zinc tin sulfur selenium (CZTSSe) thin film solar cell in Example 7. DETAILED DESCRIPTION
[0051] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0053] In this example, the reagents and experimental equipment used are shown in Tables 1-3 below.
[0054] Table 1: Detailed information of experimental reagents
[0055] Table 2: Main experimental equipment used in the experiment
[0056] Table 3: Main test equipment in the experiment
[0057] Example 1 Preparation of CZTSSe thin film solar cell device like Figure 1 As shown, the CZTSSe thin film solar cell device was first prepared according to the following experimental steps: Choose 20×20×2 mm 3 Soda-lime glass (SLG) is used as a substrate. It is placed on a special PTFE rack and placed in a beaker filled with detergent water. The beaker is placed in a 60°C water bath and heated for 3 hours. After that, the glass slide is taken out and scrubbed to remove dust and oil on the surface, ensuring that there are no impurities and detergent residues visible to the naked eye on the surface of the SLG. Then, it is repeatedly rinsed with a large amount of deionized water until a uniform water film can be formed on the surface of the SLG. Next, a clean SLG is placed on a PTFE sample rack and placed in a clean beaker. Methanol, acetone and isopropanol are added and ultrasonically treated for 2-3 hours to remove impurities and organic matter on the surface. Finally, the clean SLG is placed in deionized water for repeated ultrasonic cleaning to ensure that there is no residual organic solvent on the surface. The clean SLG after cleaning can be placed in an ethanol solution for standby use.
[0058] After the prepared clean SLG was blown dry with nitrogen gas, the ethanol on the surface was quickly placed in the DC sputtering vacuum chamber. When the vacuum degree in the vacuum chamber reached 3×10 -4 After pa, the Mo back electrode is coated on the SLG using DC sputtering technology. The sputtered Mo back electrode adopts a double-layer structure: the bottom layer is a tightly crystallized Mo layer attached to the glass substrate, and the sputtering conditions of high power and low pressure are used to improve the adhesion of the Mo layer on the glass substrate to ensure that the Mo layer will not fall off during the selenization process of the precursor film; the top layer is a loose Mo layer in contact with the bottom of the absorption layer, and the sputtering conditions of low power and high pressure are used to reduce the resistance of the back electrode, thereby reducing the series resistance of the CZTSSe thin-film solar cell, and improving the fill factor and short-circuit current density. After the preparation of the Mo back electrode is completed, the substrate is placed in a vacuum drying oven for standby.
[0059] The CZTS precursor solution was prepared in air. The specific steps were as follows: First, 1.084 g C4H6CuO4·H2O and 0.74 g SnCl2·2H2O were added to 10.79 mL DMF and stirred until completely dissolved. Subsequently, 2.126 g SC(NH2)2 was added to the above solution and continued to stir until completely dissolved. Finally, 0.61 g ZnCl2 was added and stirred until completely dissolved to obtain the CZTS precursor solution. In a glove box filled with nitrogen, the CZTS precursor solution was dripped onto the SLG substrate coated with the Mo back electrode. Spin coating was performed using a spin coating instrument, with the rotation speed set to 3000 r / min and the rotation time set to 30 s. After the spin coating step was completed, the sample was placed on a hot plate and baked for 3 min at a baking temperature of 400~430°C. The above spin coating and baking steps were repeated 10 times to obtain a CZTS precursor film. The prepared precursor film was placed in a graphite box filled with selenium particles, and the graphite box was placed in a rapid annealing furnace (RTP). In a nitrogen atmosphere at normal pressure, the temperature was quickly raised to 550°C and maintained for 900 s. The sample was cooled naturally, and finally a CZTSSe absorption layer film with a thickness of about 1.2 µm was obtained.
[0060] A 60 nm thick CdS buffer layer was prepared on the surface of the absorber layer using conventional chemical bath deposition (CBD). The chemical bath consisted of 12.5 mL NH3·H2O, 0.0768 g CdSO4·8 / 3H2O, 0.11 g SC(NH2)2, and 250 mL deionized water. The reaction bath temperature was maintained at 65°C. When the CdS buffer layer reached a purple-blue color, the reaction was considered to be complete and a heterojunction was formed. A transparent conductive top contact layer was constructed using radio frequency magnetron sputtering technology to contact the CdS layer. The window layer consisted of 50 nm i-ZnO and 300 nm ITO, and the vacuum degree was maintained at 4×10 -4 pa, sputtering was performed using a sputtering power of 100 W / 100 W respectively. A metal mask plate mask of about 120 nm Ag was prepared on the window layer using a vacuum evaporation method. After the above steps, the CZTSSe thin film solar cell device was successfully assembled. All devices have no magnesium fluoride (MgF2) reduction layer, and the final structure of the device is SLG / Mo / CZTSSe / CdS / i-ZnO / ITO / Ag. The CZTSSe solar cell device was cut into individual cells using a mechanical scribing method. Each device has 9 cells, and the total area of each cell is 0.21cm 2 .
[0061] Example 2 Investigation of drug feed ratio and precursor solution aging time 1. Experimental content: This example mainly explores the Zn / Sn ratio during the drug feeding process, that is, the molar ratio of the Zn / Sn element. The remaining experimental steps are the same as those in Example 1. The specific experimental research ratios are shown in Table 4 below: Table 4: CZTS drug feed weight at different Zn / Sn ratios
[0062] At the same time, a drug with a Zn / Sn ratio of 1.35 was selected to prepare a CZTS precursor solution. In this embodiment, 9 groups of control experiments were set up, and the CZTS precursor solution was placed in the air for 0, 6, 12, 18, 24, 30, 36, 42 and 48 hours, respectively, and then the subsequent spin coating step was performed. The 9 groups of comparative experimental precursor films were placed in a graphite box filled with selenium particles at the same time, and heated at 550°C for 900 s to obtain a CZTSSe film with a thickness of about 1.2 μm. And the final CZTSSe thin film solar cell device assembly was performed (same as Example 1). The aging time sample was named: the aging time of the precursor solution was named "S-xh", and accordingly, the CZTSSe absorption layer film prepared by "S-xh" was named "CZTSSe-xh", and the CZTSSe thin film solar cell device assembled by "CZTSSe-xh" was named "Cell-xh". For example, the CZTS precursor solution with an aging time of 6 hours is named "S-6h", the CZTSSe absorption layer film prepared from S-6h is named "CZTSSe-6h", and the CZTSSe thin film solar cell device assembled from "CZTSSe-6h" is named "Cell-6h". And so on.
[0063] 2. Results 2.1. The statistical distribution of various electrical parameters of CZTSSe thin-film solar cells with Zn / Sn ratios of 1.15, 1.25, 1.35, and 1.45 in the CZTS precursor solution and the optimal single-cell electrical parameters are shown in Table 5. The results show that with the gradual increase of the Zn / Sn ratio, the device efficiency gradually increases. The optimal Zn / Sn ratio is 1.35, and the device photoelectric conversion efficiency (PCE) reaches 7.05%.
[0064] Table 5: Summary of electrical parameters of CZTSSe thin film solar cells with Zn / Sn ratios of 1.15, 1.25, 1.35, and 1.45
[0065] To further improve the device performance, CZTSSe thin film solar cells with Zn / Sn ratios of 1.35, 1.40, and 1.45 were prepared. The experimental results are shown in Table 6 below. The CZTSSe thin film solar cell device with a Zn / Sn ratio of 1.35 performed best. As the Zn / Sn ratio increases, the secondary phase ZnSe increases accordingly, and the series resistance (R S ) and the reverse saturation current density (J0) also increase. The open circuit voltage (V OC ), short-circuit current density (J SC ) and fill factor (FF) decreased, and the device performance decreased. Finally, the optimized CZTS precursor solution Zn / Sn drug feed ratio was 1.35, and the device V OC is 409.52 mV, J SC It is 36.49 mA / cm², FF is 59.29%, and PCE reaches 8.86%.
[0066] Table 6: Summary of electrical parameters of CZTSSe thin film solar cells with Zn / Sn ratios of 1.35, 1.40, and 1.45
[0067] 2.2, such as Figure 2 As shown in Figure 2, the surface and cross-sectional morphology of CZTSSe-xh are shown. It can be observed that the absorption layer film of CZTSSe-xh is composed of two grain layers, with a dense large grain layer on the top and a dense small grain layer on the bottom. This is because the CZTSSe absorption layer film is prepared using a two-step method. First, a CZTS precursor film is prepared, and then a selenization rapid annealing is performed to form a CZTSSe absorption layer. During the annealing process, the grains grow from the top to the bottom and from the bottom to the top. As shown in Figure 2 (b), holes appear in the CZTSSe film with an aging time of more than 6 hours, resulting in the exposure of the bottom grain layer. These holes will be filled with CdS deposited later, providing a channel for leakage current transmission; when the aging time exceeds 30 hours, a gap appears between the two layers, and it expands with the extension of the aging time, resulting in poor contact between the upper and lower layers, hindering the transmission of charge carriers to the Mo back electrode, and ultimately reducing the performance of the CZTSSe thin film solar cell.
[0068] As the aging time increases, the internal elements of the CZTSSe absorber layer film gradually become unbalanced, which may produce potential secondary phases and defects. Therefore, the element composition distribution of the absorber layer film prepared by aging the precursor for 6 hours is optimal, which inhibits the Cu 2+ The generation of ions reduces the formation of CuxSe secondary phase on the surface of the absorption layer film.
[0069] The performance of CZTSSe thin film solar cells increases with the aging time and starts to decline after 6 hours of aging. The average PCE increases from 7.05% (Cells-0h) to 8.02% (Cells-6h). The highest photoelectric conversion efficiency of a single cell reaches 9.10%.
[0070] Example 3 Hydrochloric acid regulation of CZTS precursor solution 1. Experimental content: 1.084 g C4H6CuO4·H2O and 0.74 g SnCl2·2H2O were added to 10.79 mL NN dimethylformamide (DMF) and stirred until dissolved. Then 2.126 g thiourea (Tu) was added and stirred until completely dissolved. Finally, 1 mL hydrochloric acid (HCl) and 0.61 g ZnCl2 were added to obtain a CZTS precursor solution regulated by hydrochloric acid. CZTSSe solar cell devices were assembled according to the experimental method in Example 1. The sample naming method is as follows: 1 mL HCl was added to the unaged precursor solution, named "With HCl"; the precursor solution without hydrochloric acid was aged for 6 hours and named "Without HCl".
[0071] 2. Results like Figure 3 Shown are the SEM cross-sectional images and top views of the CZTSSe absorber layer films of the Without HCl and With HCl samples. Figure 3 (a) and (c) show that the CZTSSe absorption layer of the With HCl sample has no obvious delamination phenomenon compared with the Without HCl. The results show that adding hydrochloric acid to the CZTS precursor solution can improve the cross-sectional morphology of the CZTSSe absorption layer, eliminate the delamination phenomenon, and thus improve the device performance. Figure 3 (b) and (d) show that the samples have strong particle density.
[0072] like Figure 4 (a) and (b) are shown in Table 7 below, which are the IV characteristic curves and PCE statistical distribution diagrams of the Without HCl and With HCl samples and the summary of solar cell electrical parameters. The average PCE is from Figure 4 The PCE of CZTSSe solar cells increased from 7.64% (WithoutHCl) in Table 7 to 9.26% (With HCl) in Table 7, and the best PCE of CZTSSe solar cells increased from 9.25% (WithoutHCl) to 9.83% (With HCl) in Table 7. This shows that the addition of hydrochloric acid to the precursor solution not only improves the overall performance of the device, but also improves the performance of a single solar cell.
[0073] With HCl J SC , Rs, A and J0 are 37.12 mA / cm 2 , 0.54 Ω·cm 2 , 1.72 and 0.0017 mA / cm 2 . This indicates that the CZTSSe solar cell with HCl sample can further reduce the surface secondary phase and defect concentration, reduce the recombination of interface carriers, thereby improving JSC and reducing Rs and J0. At the same time, the value of A is reduced to less than 2, indicating that the carrier recombination problem is transferred from interface recombination to bulk recombination, and the surface quality of the CZTSSe absorption layer film has been greatly improved, which can better match the interface of Mo / CZTSSe and CZTSSe / CdS.
[0074] CV test curve, depletion layer width and free carrier density are shown in Figure 4 (c) The carrier concentration can be determined by the y value at 0 V. Adding hydrochloric acid to the precursor solution can effectively increase the carrier concentration and the depletion layer width. The carrier concentration without HCl is calculated to be 5.69×10 16 cm -3 , the carrier concentration with HCl increases rapidly to 1.16×10 17 cm -3 , the depletion layer width (Wd) increases from 149.79 nm to 165.37 nm, which is consistent with the Hall test law. The photogenerated carrier concentration increases and the carrier recombination decreases. At the same time, the device efficiency standard deviation is as follows Figure 4 (d) As shown. With HCl, the device efficiency is uniform, and the standard deviation is less than 0.5. These results all show that hydrochloric acid regulates the CZTS precursor solution environment and effectively suppresses the Cu 2+ The association reaction of Tu and (-COOH) makes Cu 2+ +Sn 2+ The redox reaction continues to Cu + +Sn 4+ Move, increase the Sn in the solution 4+ The content of Sn is related to V Sn (- / 0), Cu Sn (- / 0) and Zn Sn The (2- / -) defect is reduced, the carrier concentration and the width of the depletion layer are increased, the concentration of carrier non-radiative recombination centers is reduced, and the performance and uniformity of CZTSSe devices are improved.
[0075] Table 7: Summary of single cell battery parameters and device average electrical parameters for Without HCl and With HCl samples
[0076] In general, the addition of hydrochloric acid to the CZTS precursor solution inhibits the association and increases the Sn 4+ The content of Sn 2+ The defects created in the CZTSSe film improve the performance of the solar cell.
[0077] Example 4 Construction of a double-layer CZTSSe absorption layer 1. Experimental content The strategy for actively constructing a double-layer CZTSSe absorption layer is to prepare a portion of the CZTS precursor film by spin coating, form the first portion of the CZTSSe absorption layer after selenization, spin coat the second portion of the CZTS precursor film on top of the first portion of the absorption layer, and then selenize to form a complete CZTSSe absorption layer. The specific experimental method is: spin coating n times to form the first portion of the CZTS precursor film, form the first portion of the CZTSSe absorption layer after selenization, spin coat the second portion of the CZTS precursor film on top of the first portion of the absorption layer 10-n times, and then selenize to form a complete CZTSSe absorption layer. The specific experimental conditions are: (1) First, the CZTS precursor film (the first part, named 3C) was spin-coated 3 times and selenized, and then the CZTS precursor film (the second part) was added 7 times and selenized, and a total of 10 spin coatings were made to form a CZTSSe absorption layer (named TFS, or 3+7).
[0078] (2) First, spin coat the CZTS precursor film (the first part, named 5C) 5 times and selenize it, then add the CZTS precursor film (the second part) 5 times and selenize it, and spin coat it 10 times in total to form a CZTSSe absorption layer (named 5+5).
[0079] (3) First, spin coat the CZTS precursor film (the first part, named 7C) 7 times and selenize it, then add the CZTS precursor film (the second part) 3 times and selenize it, and spin coat it 10 times in total to obtain the CZTSSe absorption layer (named 7+3).
[0080] (4) The CZTS precursor film was spin-coated 10 times and selenized to form a CZTSSe absorption layer (named BASIC).
[0081] The optimal condition is to spin-coat the CZTS precursor film (0.6 µm) three times for the first selenization, then add the CZTS precursor film (1.4 µm) seven times for the second selenization, and spin-coat 10 times in total to form a CZTSSe absorption layer (named 3+7 or TFS). The preparation flow chart is shown in Figure 5 The remaining steps for preparing the CZTSSe thin film solar cell are the same as the experimental method in Example 1.
[0082] The CZTS precursor film prepared by spin coating 10 times was subjected to two consecutive selenization processes, and the prepared absorption layer sample was named DA. It was further compared and analyzed with TFS and BASIC samples. The preparation flow chart of CZTSSe absorption layer is shown in Figure 5. The remaining steps of preparing CZTSSe thin film solar cells are the same as the experimental method of Example 1.
[0083] 2. Results from Figure 6 The results show that there are obvious differences on the surface of the CZTSSe absorption layer. The grains of the first absorption layer (3C, 5C, 7C and BASIC) gradually increase with the increase of the number of spin-coating layers. However, with the increase of the number of spin-coating layers in the first part (3+7, 5+5, 7+3), the grains of the complete absorption layer gradually become smaller and the density decreases.
[0084] like Figure 7 As shown, the surface grains of the four samples are not much different, but the surface grains of the 3+7 sample are the most dense and have the least holes, which is beneficial to the reduction of device leakage current. From the cross-sectional SEM image, it is found that only the 3+7 sample successfully constructed a double-layer absorption layer film, and the bottom grain layer is obviously denser and flatter than the BASIC sample. For the 5+5 and 7+3 samples, although the double-layer absorption layer was not successfully constructed, a grain layer running through the top and bottom was obtained. Due to the large number of holes in the absorption layer, the device leakage current is large. Therefore, by spin-coating the CZTS precursor film (the first part, named 3C) 3 times and selenizing, and then adding the CZTS precursor film (the second part) 7 times and selenizing, a total of 10 spin coatings, the process of making the CZTSSe absorption layer can prepare a double-layer absorption layer structure with large crystals and dense grains.
[0085] In addition, the Raman spectra of BASIC, TFS and DA samples were fitted by Lorentz fitting and showed that A 162 / (A 162 +A 187 ) ratio gradually decreased from 0.294 to 0.220. 162 / (A 162 +A 187 ) ratio decreases, the concentration of CuZn shallow level defects decreases, thus providing potential advantages for the performance of CZTSSe solar cells. 236 / (A 236 +A 187 ) has a maximum value of 0.131, which indicates that Zn Sn The concentration of Sn increases, resulting in deep level defects Zn Therefore, the strategy of actively constructing a double-layer CZTSSe absorption layer reduces the concentration of Cu ZnThe shallow level defect concentration increases the carrier concentration. At the same time, the deep level defect Sn is reduced. Zn concentration, thereby reducing the recombination of carriers.
[0086] In order to further study the effects of the secondary selenization process and the active construction of a double-layer CZTSSe absorber on the grain microstructure, the surface and cross-sectional images of the CZTSSe absorber were characterized using a scanning electron microscope. Figure 8 As shown in (a) and (c), compared with TFS, the surfaces of BASIC and DA exhibit a series of pores and voids. The TFS sample has uniformly dense and flat grains, which is beneficial to the performance of CZTSSe solar cells. Figure 8 From the SEM cross-sectional images of (d), (e) and (f), all three samples show delamination of the CZTSSe absorber layer. The upper layer shows high crystallinity and large grain size, while the lower layer is composed of smaller particles in the BASIC sample. In contrast, both the TFS and DA samples have large and dense grains at the bottom of the absorber layer, which is a significant improvement over BASIC. This suggests that the secondary selenization process can improve the crystallinity of the bottom layer. Due to their larger size and increased density, the grains at the bottom of the absorber layer produce fewer grain boundaries, reducing the possibility of carrier recombination during reverse transport. This further reduces the leakage current consumption and improves the performance of CZTSSe solar cells. The secondary selenization process is key to forming a dense grain layer at the bottom, while the active construction of a double-layer absorber strategy can form a dense grain layer without holes on the top.
[0087] from Fig. 9 (a) It can be clearly seen that the TFS cell has better photovoltaic performance than the BASIC cell. Table 8 below lists the detailed electrical parameters of representative CZTSSe solar cells using the two strategies. BASIC sample V OC is 410.05 mV, J SC 38.65 mA / cm 2 , the filling factor (FF) is 55.09% and the PCE is 8.76%. However, by constructing a double-layer absorber, the quality of the CZTSSe absorber layer is improved and the Cu Zn and Sn Zn defect concentration, the photoelectric conversion efficiency is increased to 10.49%, V OC , J SC and FF were 439.44 mV and 39.73 mA / cm 2 and 58.13%. OC , FF and J SC The contribution to the improvement of the photoelectric conversion efficiency from BASIC to TFS is estimated to be 40.19%, 21.75% and 38.05%, respectively.OC , FF and J SC With the enhancement, the performance of TFS is significantly better than that of BASIC. At the same time, the device uniformity is also greatly improved, and the standard deviation of device efficiency is reduced from 0.76 to 0.32. Fig. 9 (b) shown.
[0088] Table 8: Device parameters of BASIC and TFS samples
[0089] In addition, TFS has a superior absorption spectrum between 500 and 1100 nm compared to BASIC due to the enhanced overall performance of the CZTSSe absorber layer. The long-wavelength absorption extends from 800 to 1100 nm, contributing to higher quantum efficiency and J SC Therefore, the strategy of actively constructing a double-layer absorber enables high-quality CZTSSe absorbers with higher light absorption efficiency. The best photoelectric conversion efficiency of CZTSSe thin-film solar cells is improved from 8.73% to 10.49%.
[0090] Example 5 Study on the baking temperature of CZTS precursor film 1. Experimental content: CZTS precursor film baking temperature experiment The preparation of the CZTS precursor solution in this embodiment is the same as the hydrochloric acid treatment experimental method of the precursor solution in Example 3. The baking temperatures after spin coating are 220° C., 240° C., 250° C., 260° C., 280° C., 300° C., and 320° C. The remaining experimental steps are the same as those in Example 1.
[0091] 2. Results According to experimental observations, it was found that at a baking temperature of 200°C, water molecules and impurities could no longer be effectively removed when the fifth layer of the precursor film was coated, so a CZTSSe solar cell with photoelectric conversion efficiency could not be formed. Fig.10As shown, at a baking temperature of 220°C, water molecules and impurities cannot be effectively removed after the eighth layer of the precursor film is coated, and therefore a CZTSSe solar cell with photoelectric conversion efficiency cannot be completely formed; at a baking temperature of 240°C, water molecules and impurities can be removed from the top portion after the tenth layer of the precursor film is coated, thereby forming a CZTSSe solar cell with photoelectric conversion efficiency; at a baking temperature of 250°C, water molecules and impurities cannot be completely removed from the top portion after the tenth layer of the precursor film is coated, but a CZTSSe solar cell with a certain photoelectric conversion efficiency can be formed; at a baking temperature of 260°C, water molecules and impurities can be completely removed from the top portion after the tenth layer of the precursor film is coated, and less metal elements in the precursor film are volatilized, thereby forming a photoelectric conversion The CZTSSe solar cell with the best efficiency; at a baking temperature of 280℃, the top part after coating the tenth layer of the precursor film can also completely remove water molecules and impurities, but the metal elements in the precursor film have a certain volatilization, forming a CZTSSe solar cell with a certain photoelectric conversion efficiency; at a baking temperature of 300℃, the top part after coating the tenth layer of the precursor film can also completely remove water molecules and impurities, but the metal elements in the precursor film have a certain volatilization, forming a CZTSSe solar cell with a certain photoelectric conversion efficiency; finally, at a baking temperature of 320℃, the top part after coating the tenth layer of the precursor film can completely remove water molecules and impurities, but the metal elements in the precursor film volatilize more, still forming a CZTSSe solar cell with a certain photoelectric conversion efficiency.
[0092] If the baking temperature is too low, the purpose of removing water molecules and impurities cannot be effectively achieved, resulting in the presence of substances such as C, H, O, N, Cl, Sx, SnS, etc. in the film, thereby affecting the ability of the absorption layer to form a large grain layer during the selenization process, resulting in poor crystallinity of the film. On the contrary, although the baking temperature is too high, although it can effectively remove water molecules and impurities, it will lead to an increase in the volatilization of metal elements in the precursor film, greatly increasing the possibility of potential defect formation. The strategy of regulating the precursor solution environment with hydrochloric acid changes the thermal decomposition characteristics of the precursor film, allowing it to be converted into the target CZTS film at a lower temperature, thereby reducing defect formation, effectively reducing the baking temperature, and improving the photoelectric conversion efficiency and performance of CZTSSe thin-film solar cells, while reducing the device preparation cost.
[0093] Example 6 Temperature Study during Selenization Cooling Stage 1. Experimental content The preparation of CZTS precursor solution is the same as the experimental method of hydrochloric acid treatment of precursor solution in Example 3. The preparation of CZTS precursor film is the same as the experimental method in Example 5, and the baking temperature is 260°C. The selenization condition is 550°C for 15 min. In this embodiment, the 550 ~ 480°C stage is stable for 3 min, so it is not discussed. The natural cooling from 200 to 25°C is named TD (Third-stage temperature-decrease process). The element diffusion reaction at this stage is extremely weak and is not discussed. The selenization cooling control experiment is divided into two parts: (1) 480 ~ 300℃ cooling control, named FD (First-stage temperature-decrease process), the details are as follows: FD-15: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ –15 min–300℃ – natural cooling – 20℃; FD-20: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ –20 min –300℃ – natural cooling – 20℃; FD-25: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ –25 min–300℃ – natural cooling – 20℃.
[0094] (2) 300 ~ 200℃ cooling control, named SD (Second-stage temperature-decrease process), the details are as follows: SD-5: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ – 1200 s –300℃ –5 min – 200℃ – natural cooling – 20℃; SD-10: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ – 1200 s –300℃ –10 min – 200℃ – natural cooling – 20℃; SD-15: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ – 1200 s –300℃ –15 min – 200℃ – natural cooling – 20℃; SD-20: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ – 1200 s –300℃ –20 min – 200℃ – natural cooling – 20℃; SD-25: 20℃ – 60 s – 550℃ – 900 s – 550℃ – 180 s – 480℃ – 1200 s –300℃ –25 min – 200℃ – natural cooling – 20℃.
[0095] The remaining experimental steps are the same as those in Example 1.
[0096] 2. Results Depend on Fig.11 As shown in (a), FD-15 has the most holes on its surface, FD-20 has no holes on its surface, and FD-15 has a small amount of holes on its surface. Fig.11 (b) It can be seen that the surfaces of FD-15 and FD-20 are relatively flat, and the grain protrusion of FD-25 is more serious. At the same time, the bottom contact of FD-15 and FD-20 is good, with a small number of holes, while the bottom contact of FD-25 is poor. Since Se still participates in the absorption layer reaction during the cooling process of 480℃-300℃, the shorter the cooling time, the longer the Se reaction time. FD-15 forms large grains at high temperature, but the reaction time is too short during cooling, and the small grains between the large grains cannot expand, resulting in the formation of holes. In FD-20, the small grains expand fully and gradually squeeze and fuse with the large grains formed at high temperature, eliminating the formation of holes and forming a dense absorption layer. In FD-25, the small grains expand excessively during this period, the stress is released upward and downward, the grains bulge severely, holes appear on the surface and it is uneven, and the bottom contact becomes worse.
[0097] Similarly, by Fig.12 It can be seen that the SD-5 absorption layer film has the least holes on the surface and excellent cross-sectional morphology.
[0098] Combination Fig.13Statistical distribution diagram of device electrical parameters. The many holes on the surface of the FD-15 absorption layer lead to the highest series resistance and low open circuit voltage, resulting in the worst device performance. The FD-25 has poor bottom contact and the worst shunt resistance, resulting in a decrease in short-circuit current, slightly poor device performance, large grain fluctuation, the largest variance of reverse saturation current and diode ideal factor, and the worst device uniformity. The FD-20 absorption layer has a dense surface, the lowest series resistance, and a higher short-circuit current. The bottom of the absorption layer has good contact, the highest parallel resistance, and a higher open circuit voltage. The absorption layer is flat, the reverse saturation current and the diode ideal factor have a small variance, and the device performance is higher. With the increase of selenization time from 480℃ to 300℃, the device efficiency gradually decreases. With the selenization time from 300℃ to 200℃, the appearance of surface holes reduces the open circuit voltage and increases the series resistance of the device. The contact at the bottom of the absorption layer deteriorates, the short-circuit current decreases, and the parallel resistance of the device decreases. The diode ideal factor and reverse saturation current gradually increase with the overall change of the absorption layer, the device fill factor decreases, and the SD-5 device has the best performance. Therefore, this embodiment optimizes the selenization process by precisely controlling the selenization process, achieves efficient light absorption and hole transport, achieves the required material properties and optimizes device performance, and realizes the stable preparation of high-efficiency CZTSSe thin-film solar cells, with the best device performance reaching 10.7%.
[0099] In this embodiment, by studying the annealing cooling stage of the CZTSSe absorption layer, the element diffusion is precisely controlled, the anion defect formation is reduced, and the 2+2-DMF system CZTSSe solar cell device efficiency of 10.00 ~ 11.00% is stably achieved, and the optimal solar cell efficiency is 11.00%.
[0100] Example 7 Study on Precise Control of Selenization Temperature 1. Experimental content The CZTS precursor solution was prepared based on the hydrochloric acid treatment experimental method of the precursor solution in Example 3.
[0101] The following four groups of selenization strategies are set. Except for the following selenization strategies, the remaining steps are the same as those in Example 1.
[0102] (1) Traditional selenization strategy: Place a certain amount of selenium (Se) particles in a graphite box and place the prepared CZTS precursor film in the graphite box. Set the RTP temperature program to heat the sample to 550°C within 60 seconds and maintain it for 900 seconds. Finally, the sample is cooled naturally. Take out the selenized CZTSSe absorption layer from the RTP and assemble the subsequent CZTSSe thin film solar cell device to obtain a high-efficiency CZTSSe thin film solar cell 7-A.
[0103] (2) Place a certain amount of selenium (Se) particles in a graphite box, and place the prepared CZTS precursor film in the graphite box. Set the RTP temperature program, heat the sample to 550°C within 60s, hold for 900s, and then cool it down according to the following program: 550°C-180s-480°C-20min-300°C-5min-200°C-natural cooling-20°C. Take out the selenized CZTSSe absorption layer from RTP, and assemble the subsequent CZTSSe thin film solar cell device to obtain a high-efficiency CZTSSe thin film solar cell 7-B.
[0104] (3) Place a certain amount of selenium (Se) particles in a graphite box, and place the prepared CZTS precursor film in the graphite box. Set the RTP temperature program, heat the sample to 480°C within 60s, and then increase it to 550°C within 180s. Subsequently, reduce the temperature to 480°C within 720s, and then continue to cool according to the following program: 480°C-20 min -300°C-5min-200°C-natural cooling-20°C. Take out the selenized CZTSSe absorption layer from RTP, and assemble the subsequent CZTSSe thin film solar cell device to obtain a high-efficiency CZTSSe thin film solar cell 7-C.
[0105] (4) Place a certain amount of selenium (Se) particles in a graphite box, and place the prepared CZTS precursor film in the graphite box. Set the RTP temperature program, heat the sample to 230°C within 30s and maintain for 180s. Then raise the temperature to 480°C within 30s, and further raise the temperature to 550°C within 180s. Then reduce the temperature to 480°C within 720s, and then continue to cool according to the following procedure: 480°C-20 min-300°C-5 min-200°C -natural cooling-20°C. Take out the selenized CZTSSe absorption layer from RTP, and assemble the subsequent CZTSSe thin film solar cell device to obtain a high-efficiency CZTSSe thin film solar cell 7-D.
[0106] The above selenization strategies (2)-(4) are combined with the optimal cooling control in Example 6 (i.e., 20 minutes from 480°C to 300°C, and 5 minutes from 300°C to 200°C), and in the present embodiments (3) and (4), the cooling time from 550°C to 480°C is further optimized; that is, in strategies (3) and (4), the temperature is increased from 480°C to 550°C in 180 seconds; the temperature is cooled from 550°C to 480°C in 720 seconds, and the total time for maintaining the temperature above 480°C is 900 seconds.
[0107] 2. Experimental results First, X-ray diffraction (XRD) was performed to characterize the Fig.14 The main peak is the Kesterite CZTSSe phase, which is identified by PDF No. 52-0868 (CZTSe) and PDF No. 26-0575 (CZTS). The intensity of the Mo(S,Se)2 peaks near 31.8° and 56.2° in 7-B, 7-C, and 7-D ( Fig.14 , marked with plum blossoms) is significantly lower than that of 7-A, indicating that the thickness of the Mo(S,Se)2 layer at the Mo / CZTSSe interface is significantly reduced. Fig.15 In the case of 7-B, 7-C, and 7-D, the characteristic peak at 162 cm -1 , 225 cm -1 、237 cm -1 The peak intensity at 7-A is significantly reduced compared with that at 7-A, indicating that the defect concentration at the CZTSSe / CdS interface is significantly reduced, reducing the Fermi level pinning. Fig.16 It can be clearly seen that the surface grain morphology of the CZTSSe absorption layer of 7-B, 7-C, and 7-D is better than that of 7-A, and the thickness of the Mo(S,Se)2 layer at the Mo / CZTSSe interface is significantly reduced. Therefore, the variable temperature selenization strategy of high-efficiency copper zinc tin sulfur selenide (CZTSSe) thin-film solar cells with synchronous optimization of the Mo / CZTSSe / CdS dual interface not only improves the carrier transport at the Mo / CZTSSe back interface. It is also beneficial to reduce the concentration of defects and clusters at the CZTSSe / CdS interface, thereby reducing the recombination of CZTSSe carriers. Fig.17 It can be seen that the photoelectric conversion of CZTSSe thin-film solar cell devices 7-B, 7-C, 7-D, especially 7-C, has been greatly improved.
[0108] Table 9 below lists the device parameters of 7-A and 7-C.
[0109] Table 9: Device parameters of 7-A and 7-C
[0110] In summary, this example further optimizes and precisely controls the selenization temperature to achieve the preparation of high-quality 2+2-DMF system CZTSSe absorption layer. Compared with 7-A, the surface defect concentration of 7-C is increased from 1.3×10 15 cm -3 Down to 3.9×10 14 cm -3 ; The carrier lifetime is increased from 59.97 µs to 694.60 µs, and the carrier extraction and collection capabilities are improved, corresponding to R shFinally, the PCE of the optimal device reaches 11.75%, which is a significant improvement in the 2+2-DMF system without a subtraction layer.
[0111] The following are the symbols that may be involved in the present invention: Photovoltaic conversion efficiency (PCE), parallel resistance (R sh )、series resistance(R S ), diode ideal factor (A), reverse saturation current density (J0), photocurrent density (J L )、Open circuit voltage(V OC ), fill factor (FF), short circuit current density (J SC ), sulfur vacancies (V S ) defects, selenium vacancies ((V Se ) defects, etc.
[0112] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0113] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a copper-zinc-tin-sulfur-selenium thin film, characterized in that: The following steps are involved: (1) Preparation of CZTS precursor: Add a divalent copper source and a divalent tin source to a solvent, stir to dissolve, then add thiourea and a zinc source, stir until completely dissolved, and obtain a CZTS precursor solution; (2) Spin coating and baking: The obtained CZTS precursor solution is spin coated on the substrate coated with the back electrode and then baked; Repeat the spin coating and baking 3 to 10 times to obtain a CZTS precursor film; (3) Selenization: Place the CZTS precursor film in a graphite box filled with selenium particles, place the graphite box in a rapid annealing furnace, heat it to 450~600℃, and perform selenization treatment; then cool it from 500~400℃ to 350℃~300℃ within 10~20min, continue to cool it to 200℃~150℃ within 5~25min, and then naturally cool it to room temperature to obtain a CZTSSe absorption layer.
2. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: In step (1), the divalent copper source is C4H6CuO4·H2O, the divalent tin source is SnCl2·2H2O, the zinc source is ZnCl2, and the solvent is DMF.
3. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: In step (1), the molar ratio of the divalent copper source to the divalent tin source is 1.35-1.45:
1.
4. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: The obtained CZTS precursor solution was placed in air for 5 to 8 h before the subsequent spin coating step.
5. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: In step (1), after thiourea is added and dissolved, hydrochloric acid is added, and then a zinc source is added. The concentration of the hydrochloric acid is 36-45 wt %, and the hydrochloric acid is added at a ratio of 0.8-1.2:10 in terms of volume of hydrochloric acid to volume of solvent.
6. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: The method further includes repeating step (2) and step (3) once to obtain a double-layer CZTSSe absorption layer; specifically, First, a portion of the CZTS precursor film is spin-coated and baked for 2 to 5 times to obtain a portion of the CZTSSe precursor film, which is then subjected to selenization treatment in step (3) to form a first portion of the CZTSSe absorption layer; the first portion of the CZTSSe absorption layer is spin-coated and baked for 5 to 8 times, and then subjected to selenization treatment in step (3) to obtain a double-layer CZTSSe absorption layer.
7. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: In step (3), the heating to 450-600° C. and selenization treatment are specifically performed as follows: First heat to 400~500℃ within 30~90s; Then the temperature is raised to 510~580℃ within 150~250s; Finally, the temperature is lowered to 500-400°C within 600-900s.
8. The method for preparing the copper-zinc-tin-sulfur-selenium thin film according to claim 1, characterized in that: In step (2), the baking temperature is 260°C.
9. A copper-zinc-tin-sulfur-selenium thin film, characterized in that: The invention is prepared by any one of the preparation methods of claims 1 to 8.
10. A copper-zinc-tin-sulfur-selenium thin film solar cell, characterized in that: Contains the copper-zinc-tin-sulfur-selenium thin film as described in claim 9.